PALAEOPHYTOLOGIA KURTZIANA. III. 10. LA TAFOFLORA PERMICA DE SIERRA DE LOS LLANOS, PROVINCIA LA RIOJA (Ameghiniana, 2013)
"The present contribution deals with the revision of the Kurtz Collection on fossil plants from Sierra de los Llanos in La Rioja Province (Fm. Arroyo Totoral). Theseplants (collected originally by the geologist G. Bodenbender in 1895) have been mentioned in several geological papers and, in 1921, illustrated but not described by Kurtz in his Atlas (plates VIII to XIII). Now, most of the specimens are available for study after 50 years; some (very few ) are possibly lost. This collection is in the Palaeontological Laboratory of Córdoba University. On the other hand, a second lot of plants, collected by G. Bodenbender from the same locality turned out in the La Plata Museum Palaeobotanical collection; it is a duplicate lot from the large original set of fossils which has been subdivided by Bodenbender. The La Platacollection was not seen by Kurtz and as there are many specimens which contribute to a better knowledge of some taxa, their study is also included in this paper.The species which have been described are: Phyllotheca leptophylla Kurtz, Asterotheca feruglioi Frenguelli, Sphenopteris sp., Gangamopteris obovata (Carr.) White, Glossopteris occidentalis White, Cordaites hislopi (Bunb.), Arberia minasica White, Paranocladus? fallax Florin and Samaropsis sp. Botrychiopsis plantiana (Carr.) Arch. and Arrondo, has been studied by the authors in a previous paper, while (Rhodea) criciumana Rigby is mentioned but not described. Most of these species are found in other Permian formations in Argentina. A correlation with the taphofloras from Tasa Cuna (Córdoba), Bajo de Veliz (San Luis) and N. Lubecka (Chubut ) is sterngthened. They all correspond to the Flora-Age Lubeckense A, established by the authors (1971). This Age is considered to be equivalent to the Lowerrnost Permian of the International scale. The Los Llanos taphoflora is comparable with some found in the Guatá Sub-Group, Tubarao Group of Brazil, mainly with those from Lauro Muller or Minas (having 7 species in common) and Criciuma or Bainha (also with 7 common species ). In the light of some recent evidences from Brazil and Argentina, it is suggested that there are many more common species between the Brazilian and Argentinian permian basins than it has been suspected up to the presento Several important collections have not been fully studied and the revision of some groups, such as Sphenopsids, Lycopsids, may bringnew evidences on more common species. Finally, all changes proposed for the old Kurtz's deterrninations are included in an appendix."